On tactics a theory of victory in battle - Friedman, B. A. (Naval Institute Press, 2017)
Originally setting out to write the very book that he would have wanted to own as a young infantryman, the author penned On Tactics as a remedy for navigating the chaotic and inchoate realm of tactical theory. Challenging centuries-old conventional wisdom regarding the principles of war, tactics, and the roles of strategy, doctrine, experiential learning, and military history, Friedman's work offers a striking synthesis of thinking on tactics as well as strategy.